1987
DOI: 10.1021/ba-1988-0217.ch019
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Interactions Between Polycyclic Arenes in Cyclophanes

Abstract: The 'iT-'iT T HE CHARACfERISTIC FEATURE OF BENZENE AND POLYCYCLIC ARENES is the 'iT-electron system. The overlapping 2pz orbitals on each sp2-hybridized carbon center generate an electron cloud over and under a planar hydrocarbon skeleton. This electronic structure favors intermolecular interactions between arenes in a face-to-face geometry (Figure 1). In an electronically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…The reduction in the D value is expected to increase with the extent of aromatic stacking interactions involving the peptide chromophore on the basis of previous studies of Lys-Trp-Lys complex formation with poly(dT) (Maki & Cha, 1983). The size of the -AD values exhibited by the quinoline chromophores of the 2QNpolynucleotide complexes is of the same order of magnitude as those previously reported for stacking interactions between Trp residues and nucleoide bases in the binding of E. coli single-stranded DNA binding proteins and poly(dT) (Khamis et al, 1987) and those measured for cyclophanes in which naphthalene rings (approximately 3.1 Á apart) are forced into stacking arrangements by out-of-plane methylene bridges (Haenel & Schweitzer, 1988). Both proximity and orientation of the interacting ring systems were found to influence the magnitude of the reduction of the zfs D parameter of the phanes relative to their monomeric units.…”
Section: Discussionsupporting
confidence: 83%
“…The reduction in the D value is expected to increase with the extent of aromatic stacking interactions involving the peptide chromophore on the basis of previous studies of Lys-Trp-Lys complex formation with poly(dT) (Maki & Cha, 1983). The size of the -AD values exhibited by the quinoline chromophores of the 2QNpolynucleotide complexes is of the same order of magnitude as those previously reported for stacking interactions between Trp residues and nucleoide bases in the binding of E. coli single-stranded DNA binding proteins and poly(dT) (Khamis et al, 1987) and those measured for cyclophanes in which naphthalene rings (approximately 3.1 Á apart) are forced into stacking arrangements by out-of-plane methylene bridges (Haenel & Schweitzer, 1988). Both proximity and orientation of the interacting ring systems were found to influence the magnitude of the reduction of the zfs D parameter of the phanes relative to their monomeric units.…”
Section: Discussionsupporting
confidence: 83%
“…The π−π* transition bands of [ n . n ]naphthalenophanes with different types of linkages show a variety of spectral patterns depending on the stacking mode of the naphthyl groups …”
Section: Resultsmentioning
confidence: 99%
“…n ]paracyclophanes with n = 1−3 show three π−π* transition bands in the spectral range 245−320 nm, in contrast to acyclic para-substituted benzene derivatives which show a single electronic band with vibrational structure in this spectral range. This abnormality of the spectra arises from the proximity of the two phenyl groups and the distortion of the phenyl rings, and it decreases with increasing length of the bridges between the phenyl groups; the spectra of paracyclophanes with n ≥ 4 are practically identical with those of acyclic p -dialkylbenzenes. Systematic studies of various types of macrocycles containing two aromatic groups in the ring systems have shown that the spectral properties are sensitive to the stacking mode of the aromatic systems . Cyclophanes that have donor groups in the ring systems undergo ring contraction upon coordination with metal ions .…”
Section: Introductionmentioning
confidence: 99%
“…The latter emission exhibits the vibrational fine structures similar to that of neutral 1 , revealing the local nature of the transition associated with the anthracene chromophore. The relative red‐shift observed for neutral 1 is attributed to the CT character of the transition involving the nitrogen's nonbonding orbital, which is missing in protonated 1‐H + . The excitation spectrum for the low‐energy transition was essentially superimposable with the UV‐vis spectrum of 1‐H + (Figure S6 in the Supporting Information), and the band was assigned to the emission from the CT state.…”
Section: Resultsmentioning
confidence: 54%
“…Pyridinophane 1 was readily protonated in the presence of fluoroboric acid to produce DA cyclophane 1‐H + . A number of cyclophanes containing anthracene unit(s) have been reported in the literature, most of which focused on the fluorescence and photochemical behaviors, while anthracenophanes with DA interaction have rarely been prepared . Naturally, a strong DA interaction, which is electrostatic in nature, is expected to occur between the anthracene and pyridinium moieties in 1‐H + .…”
Section: Introductionmentioning
confidence: 99%